2021
DOI: 10.3390/ijerph181910290
|View full text |Cite
|
Sign up to set email alerts
|

Operating Room Nurses Want Differentiated Education for Perioperative Competencies—Based on the Clinical Ladder

Abstract: Operating room (OR) nurses’ perioperative competence is vital in operation and patient care. This cross-sectional descriptive study aimed to identify perioperative competencies and educational needs for improving competencies according to the clinical ladder. A total of 318 OR nurses in Korean tertiary hospitals were recruited. Data from the self-reported questionnaire of perioperative competencies, measured on a five-point Likert scale, were used. The average score of perioperative competence was 3.78 ± 0.54;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
5
8
0
Order By: Relevance
“…This finding is consistent with that reported by Juang [ 9 ]. In addition, nurses with a higher score in the sense of achievement section were more willing to participate in the program, which is consistent with the finding of Shin et al [ 22 ]. Regarding stress derived from the promotion assessment, the case report writing item had the highest score, suggesting that this was the primary source of stress affecting nurses’ willingness to participate.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is consistent with that reported by Juang [ 9 ]. In addition, nurses with a higher score in the sense of achievement section were more willing to participate in the program, which is consistent with the finding of Shin et al [ 22 ]. Regarding stress derived from the promotion assessment, the case report writing item had the highest score, suggesting that this was the primary source of stress affecting nurses’ willingness to participate.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies suggested that nurses recognize the effectiveness of the clinical ladder program in enhancing professional competence [ 1 , 9 ]. Other studies highlighted that when job levels were divided based on personal ability, nurses’ clinical experience and abilities were not only recognized, giving them a sense of belonging, but on a personal level, nurses also obtained a sense of achievement [ 9 , 22 ]. Juang [ 9 ] found that nurses felt a sense of achievement when participating in the clinical ladder program, and that advancing their professional competence and receiving approval and respect were particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, perioperative nurses who did not participate may have a different perspective and experience of perceived perioperative competence from those who did. However, our results show similar findings when larger samples (Gillespie et al, 2012; Jaensson et al, 2018) and smaller samples are used (Blomberg et al, 2019; Shin & Kim, 2021; Sönmez & Ayoğlu, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…Finally, in addition to the fit statistics indicating acceptable fit above prespecified cut‐offs supporting the construct validity of the scale, convergent and criterion validity was also met, where we found statistically significant associations for those with higher PPC‐R‐SF scores, also reported higher general self‐efficacy, have more experience in the OR, hold a postgraduate level of education and had received perioperative speciality training in the past 3 years. Similar findings of perceived competence have been reported in other research (Blomberg et al, 2019; Falk‐Brynhildsen et al, 2019; Gillespie et al, 2018; Jaensson et al, 2018; Shin & Kim, 2021; Sönmez & Ayoğlu, 2019), which was why these were considered as criteria to examine.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation